PENGEMBANGAN SISTEM PENGUJIAN MENGUNAKAN MOODLE UNTUK MENINGKATKAN EFEKTIFITAS DAN EFISIENSI UJIAN HARIAN (Studi pada mata pelajaran Simulasi digital pada Kelas X di SMK Kota Bengkulu) - Erawan Putra; Alexon Alexon (UNIB Press, 2020)
This study aims to describe,the development of testing system by usig moodleto improve the effeectiveness and efficiency of the daily examinations Digital Simulation sibjects. This research uses Research and Development (R & D) research with Borg & Gall development model in class X TKJ Bengkulu city, SMKN 3 Bengkulu city, SMKN 4 Bengkulu city. This study used steps of prelminary research, initial information collecting, planning, initial product format development, initial trials, product revisions, field trials , product revisions, preliminary form of product, preliminary field testing, main product revisions, field trials, refinement of final products and implementation. The instruments used questionnaires, observation sheets expert judgment questionmaires and test questions the data analysis technique used the percentage and t - test with the SPSS peogram. The results showed that moodle – based tet material development can improve the effectivenees and effeiciency of daily exams.